Pengaruh Layanan Jasa Keuangan PosPay dan Kurir PosAja Terhadap Tingkat Pendapatan Pada PT. Pos Indonesia Langsa - Frinal Saputri, Dea; Samri Juliati Nasution, Yenni; Sudiarti, Sri (Indonesian Journal of Islamic Economics and Business, 2023)
This study aims to examine the effect of E-Commerce services in the form of PosPay Financial Services (JASKUG) and PosAja courier services on Income Levels at PT. Pos Indonesia KC Langsa. While the research method uses a quantitative research approach. In this study using primary data, namely distributing questionnaires. The population in this study were PosPay and PosAja users, totaling 50 people, the number of samples used was 50 respondents. The method of analysis is using multiple linear regression analysis with SPSS 23. The results show that the results of the coefficient of determination (Adjusted R2), that e-commerce PosPay(X1) and e-commerce PosAja(X2) simultaneously affect the level of income (Y) is 70.2%, while the remaining 29.8% is influenced by other variables not explained in this study. PosPay e-commerce test results (X1) on income levels (Y) Tcount<Ttable with a value of -0.007<2.011 and arithmetic significance value>table significance value 0.994>0.05 means that PosPay E-Commerce has no effect and is not significant to Income Level, PosAja e-commerce (X2) to Income Level (Y) obtained Tcount>Ttable with a value of 6.758> 2.011 and a calculated significance value <table significance value 0.00 <0.05 means that PosAja E-Commerce is influential and significant on Income Level, the F test obtained an Fcount value of 22.867> Ftable of 3.19 and a Sig F value of 0.000 <0.05 there was a significant effect of PosPay E-Commerce and PosAja E-Commerce simultaneously on PT. Pos Indonesia KC Langsa.